Characterization of Pt-doped WO3nanoparticles synthesized by flame spray pyrolysis - Thanittha Samerjai (2018)
Undoped WO3and WO3nanoparticles doped with 0.25-1.0 wt.% Pt were successfully produced in a single step by flame spray pyrolysis (FSP) [1]. Tungsten (VI) ethoxide 5% w/v in ethanol 99.8% and platinum (II) acetylacetonate were used as W and Pt precursors respectively dissolved in ethanol. The undoped WO3and Pt-doped WO3nanoparticles were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and energy dispersive spectroscopy (EDS). The BET surface area (SSABET) of the nanoparticles was measured by nitrogen adsorption. From BET measurement, SSABETincreased and dBETdecreased with increasing Pt concentration from 0 to 1.0 wt.%. The morphology and accurate size of the primary particles were further investigated by high-resolution transmission electron microscopy (HRTEM). The crystallite size of undoped WO3spherical was found to be ranging from 5-20 nm and the crystallite sizes of 0.25-1.0 wt.% Pt-doped WO3spherical particles were found to be in the range of 5-20 nm. © (2012) Trans Tech Publications.